Evaluate the Implant Failure Rate of Radiotherapy Administered after Mastectomy in Breast Cancer Patients: A Systematic Review and Meta-analysis - Yasaman Shariati; Somaye Jamali; Majid Hajizadeh (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: It is currently unclear which risk factors lead to problems with breast implant reconstruction and failure of prosthetic reconstruction. The connection between radiation and complications has not yet been comprehensively investigated. This study explored the implant failure rate of radiotherapy administered after mastectomy in breast cancer patients.Material and methods: For this systematic review and meta-analysis study, international databases such as MEDLINE (PubMed and Ovid), Web of Science, and Scopus were searched until August 2024 using keywords relevant to the study objectives. STATA/MP. v17 software was used to analyze data.Results: The present study included twelve retrospective studies Among 5113 patients (5180 reconstructed breasts) with the mean age ranging from 36.7 to 55.6 years. Irradiated breasts were 0.32 times more vulnerable to developing capsular contracture than non-irradiated breasts (RR, 0.32; 95% CI, 0.04-0.61; p=0.03). The risk ratio of seroma was -0. 40 (RR, -0.40; 95% CI -0.78, -0.02; p=0.04) and The Reconstruction failure was associated with received radiotherapy (OR =0.44; 95% CI: 0.21, 0.66; p<0.01; I2 = 83.87%, p<0.01).Conclusions: According to the results of the present meta-analysis, post-mastectomy radiotherapy can increase implant reconstruction failure.